Employment Participation and Determinants of the Gender Wage Gap in the Head of the Household - Jihad Lukis Panjawa; Retno Sugiharti; Jalu Aji Prakoso; Muhammad Arif Kurniawan (Universitas Ahmad Dahlan, 2022)
The distortion model becomes a problem in development planning, including in the development goals of reducing discrimination and concerns. These two things are closely related to gender expectations on work participation. The purpose of this study was to estimate the gender pay gap at the work participation rate of household heads in Magelang during the Covid-19 pandemic. The analytical tools used are Probit regression and the decomposition of the Blinder-Oaxaca model. The model decomposes wage differentials by gender. The study uses the 2020 SAKERNAS data. The results show that work participation for male household heads is determined by the marginal effect of work experience, age and area of residence, not education level and number of family dependents, while female household heads are only determined because of the number factor. family responsibilities. Furthermore, the potential work experience of male household heads has a significant negative effect. Research findings from the Blinder-Oaxaca Decomposition calculation show that the difference in wages between groups of household heads during the Covid 19 pandemic proved statistically significant. The role of the government is expected to be more active in disseminating policies related to gender in the labor market and exercising control over business actors in implementing labor regulations.